2013
DOI: 10.1016/j.jpsychores.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Associations between DSM-IV mental disorders and onset of self-reported peptic ulcer in the World Mental Health Surveys

Abstract: Objective Recent research demonstrating concurrent associations between mental disorders and peptic ulcers has renewed interest in links between psychological factors and ulcers. However, little is known about associations between temporally prior mental disorders and subsequent ulcer onset. Nor has the potentially confounding role of childhood adversities been explored. The objective of this study was to examine associations between a wide range of temporally prior DSM-IV mental disorders and subsequent onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It is only by using survival analysis that we are able to exclude such episodes from the predictor set because the data are organised in person-year files. Comparable with previous studies using these data [26, 27], we used discrete-time survival analyses [28] with person-year as the unit of analysis to test associations between first onset of mental disorders and diabetes diagnosis. For these analyses, a person-year dataset was created in which each year in the life of each respondent up to and including the age of onset of diabetes or their age at interview (whichever came first) was treated as a separate observational record, with the year of diabetes onset coded 1 and earlier years coded 0 on a dichotomous outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…It is only by using survival analysis that we are able to exclude such episodes from the predictor set because the data are organised in person-year files. Comparable with previous studies using these data [26, 27], we used discrete-time survival analyses [28] with person-year as the unit of analysis to test associations between first onset of mental disorders and diabetes diagnosis. For these analyses, a person-year dataset was created in which each year in the life of each respondent up to and including the age of onset of diabetes or their age at interview (whichever came first) was treated as a separate observational record, with the year of diabetes onset coded 1 and earlier years coded 0 on a dichotomous outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…Of four studies reporting the association of PTSD with type 2 diabetes mellitus, three (75%) provided positive findings (23, 68, 69), one (25%) provided negative findings (58), and none reported mixed findings (Table 2 and Online Data Supplement Table 3). All four studies that reported on the association of PTSD with gastrointestinal ulcer diseases were positive (21, 62, 70, 71) (Table 2 and Online Data Supplement Table 4). Finally, all three studies (100%) that examined PTSD as a risk factor for dementia reported positive findings (7274).…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional design also raises the possibility of spurious or inflated associations through mental disorders at the time of interview affecting self-report of physical conditions; however, sensitivity analyses excluding individuals with mental disorders at the time of the interview found no meaningful alteration in associations. 9 …”
Section: Discussionmentioning
confidence: 99%